Integrated Waste Management System with IOT-Based Centralized Control towards a Smart Eco Campus-Telkom University - Permana, Agus Ganda; Raharjo, Jangkung (International Journal of Energy Economics and Policy, 2023)
Telkom University is a private university in Indonesia that has implemented an eco-campus or green campus program. The Greenmetric Program is one part of Telkom University’s strategic planning in realizing a campus that cares and has an environmental culture by managing the environment in a systematic and sustainable manner. One of the programs is to reduce waste production. Therefore, it is necessary to conduct research related to optimizing waste management by implementing Onsite Waste Treatment Technology-Integrated-Independent-Environmentally Friendly (TOSS-TMRL). TOSS-TMRL Management System with Centralized Control Based on the Internet of Things (IoT) Towards a Smart ECO Campus to be completed on the spot. This will reduce pollution, operational costs, and waste management investment and can even function as Living Labs for environmental-based courses. In addition, optimization is also one of the efforts to realize a smart eco campus towards the best-ranking Green Metric Telkom University. Wireless communication technology is very efficient, effective, and easy to use. One of the applications can be applied to determine the condition of environmental cleanliness in a campus area by integrating microcontroller technology and detection devices (sensors, QR codes, AR/imaging, and CCTV) with Wireless Sensor Networks (WSN) and IoT applications as tools to increase awareness of the importance of sorting waste so that the cleanliness of the campus area can be maintained. In this study, a system and network architecture design were carried out based on the number of sensor nodes, the number of recycle bins, the number of garbage transportation equipment, the number of buildings, the number of areas, and the ability of Data Transfer Nodes (DTN) to provide information to the server taken from the recycle bin of each room/building, business areas, SME facilities, canteens, and dormitories or local areas. With this system, it is hoped that there will be no accumulation of garbage and allow users/garbage managers to interact with the system through a web browser and android application.